TINJAUAN ONTOLOGIS ATAS KAJIAN INTEGRASI ISLAM DAN PSIKOLOGI : (Ontological Review of Integration Studies Islam and Psychology) - Jamil Abdul Aziz; Muhammad Safri Jamal (Raqib: Jurnal Studi Islam, 2024)
The discourse on the concept of the integration of Psychology with Islam (ontology) in Indonesia from the beginning of its emergence in the 90s until now has never really got a single point of agreement or meaning. The most powerful debate crystallized in two groups, namely: "Islamic Psychology" and "Islamic Psychology". The "Islamic Psychology" group argues that the starting point for the integration of Psychology and Islam is in the Science of Psychology which is then analyzed by Islamic studies. Meanwhile, the "Islamic Psychology" group, on the other hand, started with Islamic studies (the Koran, Hadith, etc.) and then approached the science of psychology. In addition, the scientific position and the formulation of the method (epistemology) of Islamic Psychology itself in the midst of the building of other disciplines is not clear. Not to mention the debate about the actual impact or contribution (axiology) of Islamic psychology itself in practical and theoretical terms. The method used in the author of this article is a literature review or library research.